An experimental work on effect of bending down conductor with reinforced concrete - Ariffen A.M.; Arshad S.N.M.; Ab Kadir M.Z.A.; Jasni J.; Halim N.H. (Institute of Physics Publishing, 2023)
Electric breakdown; Lightning protection; Walls (structural partitions); Air-termination systems; bent effect; Down-conductors; Impulse voltage; Lightning currents; Lightning protection systems; Reinforcement bar; Reliability and safeties; Reinforced concrete